The Relationship Between Work Stress and Workload with Job Embeddedness Among Generation Z Employees in the Creative Media Industry of Cirebon - Siti Rikhanah; Agi Syarif Hidayat (Asian Journal of Management Analytics, 2026)
This study examines the relationship between work stress, workload, and job embeddedness among Generation Z employees in creative media companies in Cirebon. Grounded in the Job Demands–Resources (JD-R) framework, the study addresses the limited evidence regarding employee attachment within regional creative media organizations. A quantitative associative approach was employed using data collected from 100 Generation Z employees through proportionate stratified random sampling. Data were analyzed using multiple linear regression. The findings reveal that work stress has a positive but insignificant relationship with job embeddedness, while workload has a positive and significant relationship with job embeddedness. Simultaneously, work stress and workload significantly influence job embeddedness. These results suggest that Generation Z employees in creative media organizations tend to perceive workload as a challenge that supports learning and professional growth rather than merely as a job demand.